Lithium metal negative electrode and preparation method thereof and lithium metal battery

By using a composite protective layer in a lithium metal battery, a composition of lithium halide, organic lithium salt and alloy components is used to form a protective layer through in-situ reaction, the problem of lithium dendrites is solved and the cycle stability and life of the battery is improved.

CN115394958BActive Publication Date: 2025-03-28CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110565047.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-24
Publication Date
2025-03-28
Estimated Expiration
2041-05-24

AI Technical Summary

Technical Problem

The growth of lithium dendrites in lithium metal batteries leads to battery life and safety issues. The protective layer combination of the prior art is weak, making it difficult to effectively inhibit the formation of dendrites.

Method used

Using a composite protective layer, a composition including lithium halide, organic lithium salt and alloy component, is formed on the surface of lithium metal by in situ reaction, and has the conductivity and electrical conductivity of the composite structure.

Benefits of technology

It effectively improves the distribution uniformity of lithium ions, delays the formation of lithium dendrites, and improves the circulation stability and cycle life of lithium metal batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium metal batteries, and discloses a lithium metal negative electrode, a preparation method thereof, and a lithium metal battery. The lithium metal negative electrode comprises at least one composite protective layer, and the composite protective layer comprises a composition containing at least two of a lithium halide, an organic lithium salt, and an alloy component, and based on the total weight of the composition, the content of the lithium halide is 25-55% by weight, the content of the organic lithium salt is 5-30% by weight, and the content of the alloy component is 30-60% by weight. The lithium metal battery has higher cycle stability and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a lithium metal negative electrode and a preparation method thereof, and a lithium metal battery. Background Art

[0002] With the development of new energy vehicles, the development of power batteries with energy density above 300Wh / kg has become the main way to increase the range of vehicles. Using metallic lithium as the negative electrode is the key to achieving a breakthrough in battery energy density. When lithium metal is used as the negative electrode of a secondary battery, repeated lithium metal deposition and dissolution occur during the charging and discharging process. However, due to the instability of the solid electrolyte interface formed by the reaction of lithium and electrolyte, lithium dendrites are easily formed, consuming the electrolyte, thus limiting the life and safety of rechargeable lithium batteries. In order to inhibit the growth of dendrites and improve the safety, utilization rate and cycle life of lithium metal batteries, various research institutions have proposed a variety of solutions to the interface problem, such as changing the composition of the electrolyte, thereby changing the composition of the solid electrolyte intermediate phase; introducing a physical barrier layer with high mechanical strength on the surface of lithium metal; constructing an artificial solid electrolyte intermediate phase; changing the current collector structure, increasing lithium deposition sites to reduce local current density, etc.

[0003] CN109004276A discloses a lithium negative electrode protective film, a preparation method and a lithium metal secondary battery. The protective film is composed of lithium salt, ionic liquid, inorganic nanoparticles and lithiation-treated Nafion polymer; however, the solution preparation process involves ball milling and other steps, Nafion lithiation and other steps, and the process is cumbersome; and it is completely through physical coating, without chemical bonding, and the interface bonding is weak.

[0004] CN106935800A discloses a protective layer for the negative electrode of a secondary lithium battery. The method is limited to a few inorganic salts, and there is no data on inhibiting dendrites to support its claimed effect. In addition, the inorganic salt layer has no chemical reaction with the lithium metal interface and only relies on physical adsorption, and also has the characteristic of weak binding to lithium.

[0005] Therefore, it is of great significance to study and develop a lithium metal anode with a stable surface protective layer. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem of dendrite growth in lithium metal negative electrodes in the prior art, and to provide a lithium metal negative electrode and a preparation method thereof, as well as a lithium metal battery, wherein the lithium metal battery has higher cycle stability and cycle life.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a lithium metal negative electrode, wherein the lithium metal negative electrode includes at least one composite protective layer, the composite protective layer includes a composition containing at least two of a lithium halide, an organic lithium salt and an alloy component, and based on the total weight of the composition, the content of the lithium halide is 25-55% by weight, the content of the organic lithium salt is 5-30% by weight, and the content of the alloy component is 30-60% by weight.

[0008] A second aspect of the present invention provides a method for preparing the aforementioned lithium metal negative electrode, wherein the preparation method comprises:

[0009] (1) contacting and mixing a metal halide with an organic solvent to obtain a mixed solution;

[0010] (2) The mixed solution is brought into contact with lithium metal for in-situ reaction to obtain a lithium metal negative electrode.

[0011] A third aspect of the present invention provides a lithium metal battery, wherein the lithium metal battery comprises the aforementioned lithium metal negative electrode.

[0012] Through the above technical solution, the technical solution of the present invention has the following advantages:

[0013] (1) The present invention obtains a lithium metal negative electrode with a composite structure through an in-situ reaction, which can simultaneously conduct lithium ions and have a certain electronic conductivity, effectively improving the uniformity of lithium ion distribution during the deposition process, thereby delaying the formation of lithium dendrites.

[0014] (2) The combination of the metal halide and the organic solvent in the present invention can form a protective layer of specific components on the surface of lithium metal, having an organic, inorganic and alloyed composite structure distribution.

[0015] (3) The lithium metal battery of the present invention has higher cycle stability and cycle life. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0017] A first aspect of the present invention provides a lithium metal negative electrode, wherein the lithium metal negative electrode includes at least one composite protective layer, the composite protective layer includes a composition containing at least two of a lithium halide, an organic lithium salt and an alloy component, and based on the total weight of the composition, the content of the lithium halide is 25-55% by weight, the content of the organic lithium salt is 5-30% by weight, and the content of the alloy component is 30-60% by weight.

[0018] The inventors of the present invention unexpectedly discovered that: on the one hand, the combined use of metal halides and organic solvents can form a protective layer of specific components on the surface of lithium metal, with a composite structure distribution of organic, inorganic and alloying; on the other hand, a lithium metal negative electrode with a composite structure is obtained by an in-situ reaction, and the negative electrode has higher cycle stability and life.

[0019] According to the present invention, preferably, based on the total weight of the composition, the content of the lithium halide is 30-50% by weight, the content of the organic lithium salt is 5-25% by weight, and the content of the alloy component is 35-55% by weight; more preferably, based on the total weight of the composition, the content of the lithium halide is 35-45% by weight, the content of the organic lithium salt is 10-20% by weight, and the content of the alloy component is 40-50% by weight. In the present invention, the contents of the lithium halide, the organic lithium salt and the alloy component are limited to the aforementioned range, so that the structure of the composite protective layer has the best ion conduction effect and a certain electronic conductivity, can reduce the overpotential of lithium in the deposition process, make the deposition process easier, and hinder the formation and growth of dendrites, thereby extending the life of the lithium negative electrode.

[0020] According to the present invention, the lithium halide is selected from one or more of chloride, bromide, fluoride and iodide of metallic lithium; preferably, the lithium halide is selected from one or more of lithium chloride, lithium bromide and lithium iodide.

[0021] According to the present invention, the organic lithium salt is a lithium salt formed by an organic solvent and lithium; preferably, the organic solvent is selected from one or more of tetrahydrofuran, polymethylpyrrolidone, dimethylformamide, polycarbonate, alcohol, ether and carboxylic acid; preferably, the organic solvent is selected from one or more of tetrahydrofuran, alcohol and carboxylic acid; more preferably, the organic solvent is selected from one or more of tetrahydrofuran, ethanol and n-pentanol; in the present invention, it is further preferred that the organic lithium salt is selected from one or more of lithium butoxide, CH3CH2OLi and lithium n-pentoxide.

[0022] According to the present invention, the alloy component is an alloy formed by lithium and a metal element; preferably, the metal is selected from one or more of aluminum, zinc, gallium, germanium, cadmium, indium and tin; preferably, the alloy component is selected from one or more of lithium aluminum alloy, lithium gallium alloy and lithium indium alloy.

[0023] The second aspect of the present invention provides a method for preparing the lithium metal negative electrode as claimed in claim 1, wherein the preparation method comprises:

[0024] (1) contacting and mixing a metal halide with an organic solvent to obtain a mixed solution;

[0025] (2) The mixed solution is brought into contact with lithium metal for in-situ reaction to obtain a lithium metal negative electrode.

[0026] According to the present invention, the metal halide is selected from one or more of chlorides, bromides, fluorides and iodides of transition metals; preferably, the metal halide is selected from one or more of fluorides, chlorides, bromides and iodides of transition metals; preferably, the transition metal is selected from one or more of aluminum, zinc, gallium, germanium, cadmium, indium and tin; more preferably, the metal halide is selected from one or more of AlCl3, InBr3 and GaI3.

[0027] The inventors of the present invention have found that the use of the metal halide specifically defined above can make the lithium metal battery containing the lithium metal negative electrode have higher cycle stability and cycle life. If copper metal is selected, it will lead to the problem of being unable to alloy with lithium; and if sodium metal is selected, it will lead to the problem of low controllability of the reaction product.

[0028] According to the present invention, the organic solvent is selected from one or more of tetrahydrofuran, polymethylpyrrolidone, dimethylformamide, polycarbonate, alcohol, ether and carboxylic acid; preferably, the organic solvent is selected from one or more of tetrahydrofuran, alcohol and carboxylic acid; more preferably, the organic solvent is selected from one or more of tetrahydrofuran, ethanol and n-pentanol.

[0029] The inventors of the present invention have found that the use of the organic solvent specifically defined above can make the lithium metal battery containing the lithium metal negative electrode have higher cycle stability and cycle life. If water is selected as the solvent, excessive Li2O will be generated, resulting in weakened alloying reaction and failure to form an effective composite structure; and if acetone is selected as the organic solvent, the role of the organic component in the composite structure will be weakened.

[0030] According to the present invention, the concentration of the mixed solution is 0.01-5 mol / L, preferably 0.02-0.6 mol / L. In the present invention, if the concentration of the mixed solution is too high, the generated composite structure will have high resistance and the polarization of the lithium negative electrode will become larger. If the concentration of the mixed solution is too low, it will lead to the problem of not being able to form an effective composite structure; in the present invention, the concentration of the mixed solution is limited to the aforementioned range, so that under the condition of forming an effective composite structure, excessive interface resistance can be avoided due to the protective layer.

[0031] According to the present invention, in step (1), the mixing is performed in a glove box filled with Ar. In addition, in the present invention, the temperature of the mixing is not specifically limited and can be performed at room temperature.

[0032] According to the present invention, in step (2), the temperature of the in-situ reaction is not specifically limited and can be carried out at room temperature.

[0033] According to the present invention, in step (2), the mixed solution is brought into contact with lithium metal by one or more of spraying, spin coating, flow coating and immersion.

[0034] According to the present invention, the preparation method further comprises: contacting the solution with lithium metal for in-situ reaction and then performing drying treatment, wherein the drying conditions include: a temperature of 30-100°C, preferably 40-100°C, and in addition, there is no specific limitation on the drying time, and complete drying is sufficient. In the present invention, preferably, the drying time is 60-720 minutes.

[0035] A third aspect of the present invention provides a lithium metal battery, wherein the lithium metal battery comprises the aforementioned lithium metal negative electrode.

[0036] According to the present invention, the lithium metal battery further comprises a positive electrode and an electrolyte.

[0037] According to the present invention, the positive electrode is prepared from a positive electrode material, wherein the positive electrode material is selected from one or more of LiFePO4, LiMn2O4, NCM, NCA and sulfur; preferably, the positive electrode material is selected from NCM and / or sulfur.

[0038] According to the present invention, the electrolyte includes a solvent and a lithium salt.

[0039] According to the present invention, the solvent is an ester solvent and / or an ether solvent; preferably, the ester solvent is selected from one or more of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC) and fluoroethylene carbonate (FEC); more preferably, the ester solvent is selected from one or more of ethylene carbonate (EC), dimethyl carbonate (DMC) and fluoroethylene carbonate (FEC).

[0040] According to the present invention, the ether solvent is selected from one or more of 1,2-dimethoxyethane (DME), dioxolane (DOL) and diethyl ether (DEE). Preferably, the ether solvent is selected from 1,2-dimethoxyethane (DME) and / or dioxolane (DOL).

[0041] According to the present invention, the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI).

[0042] According to the present invention, in the electrolyte, the concentration of the lithium salt in terms of Li is 0.1-7 mol / L, preferably 0.5-4 mol / L. In the present invention, the concentration of the lithium salt is controlled within the aforementioned range, which can ensure that the viscosity of the electrolyte is not too high and that there is a sufficient number of lithium ions distributed at the interface deposition site, which is conducive to the deposition of lithium metal.

[0043] According to the present invention, the lithium metal battery is prepared for testing.

[0044] According to the present invention, the assembled battery comprises: lithium metal foil is spread out and punched into round pieces with a diameter of 12 mm, which are assembled into symmetrical button batteries.

[0045] In addition, the assembled symmetrical button cell was subjected to AC impedance test and charge-discharge cycle test. The frequency range of AC impedance test was 0.1Hz-1MHz, and the bias voltage was 5mV. The current density of constant current charge-discharge test was 0.1-5mA / cm 2 .

[0046] The present invention will be described in detail below through examples.

[0047] In the following examples and comparative examples:

[0048] (1) Lithium deposition overpotential test in the first week:

[0049] The symmetrical battery was tested by a Landian charge and discharge tester (Wuhan Landian LAND CT2001) at a current density of 1 mA / cm 2 When the overpotential value of lithium deposition is obtained, the test is performed.

[0050] (2) Life test of lithium negative electrode

[0051] The symmetrical battery was tested by a Landian charge and discharge tester (Wuhan Landian LAND CT2001) at a current density of 0.1-5 mA / cm 2 , lithium deposition capacity is 1 mAh / cm 2 The cycle stability of the battery was tested under the conditions of .

[0052] (3) Interface impedance test

[0053] The symmetrical battery was tested by Auto-Lab electrochemical workstation (PGSTAT302N, Metrohm, Switzerland). The test conditions included a test frequency of 0.1 Hz-1 MHz and a bias voltage of 5 mV.

[0054] Example 1

[0055] This embodiment is intended to illustrate a lithium metal battery prepared using the lithium metal negative electrode of the present invention.

[0056] (1) In a glove box filled with Ar, AlCl3 was dissolved in THF to prepare a 0.02 mol / L mixed solution;

[0057] (2) 50 μL of the mixed solution was sprayed onto the surface of a 16 mm lithium metal disc for in-situ reaction. After the reaction was completed, the disc was dried at 40° C. in a glove box.

[0058] As a result, a lithium metal negative electrode with a composite protective layer structure is obtained, wherein the ratio of lithium halide (specifically LiCl): organic lithium salt (specifically lithium butoxide): alloy component (specifically LiAl alloy) is 40:10:50.

[0059] In addition, the lithium metal anode is used to prepare a lithium metal battery:

[0060] The electrolyte was 1 mol / L LiPF6 EC / DEC solution, and the battery was assembled into a symmetrical battery for charge and discharge cycle testing at 1 mA / cm 2 At a current density of , the lithium deposition overpotential in the first week was 0.15 V, the average deposition overpotential during the long-term cycle was 0.1 V, and no short-circuit signal occurred after 100 cycles.

[0061] Example 2

[0062] This embodiment is intended to illustrate a lithium metal battery prepared using the lithium metal negative electrode of the present invention.

[0063] (1) In a glove box filled with Ar, InBr3 was dissolved in ethanol to prepare a 0.6 mol / L mixed solution;

[0064] (2) 50 μL of the mixed solution was sprayed on the surface of a 16 mm lithium metal disc for in-situ reaction. After the reaction was completed, the disc was dried at 80° C. in a glove box.

[0065] As a result, a lithium metal negative electrode with a composite protective layer structure is obtained, wherein the ratio of lithium halide (specifically LiBr): organic lithium salt (specifically CH3CH2OLi): alloy component (specifically LiIn alloy) is 35:20:45.

[0066] In addition, the lithium metal anode is used to prepare a lithium metal battery:

[0067] The electrolyte was 1 mol / L LiPF6 EC / DEC solution, and the battery was assembled into a symmetrical battery for charge and discharge cycle testing at 1 mA / cm 2 At a current density of , the lithium deposition overpotential in the first week was 0.12 V, the average deposition overpotential during the long-term cycle was 0.08 V, and no short-circuit signal occurred after 180 cycles.

[0068] Example 3

[0069] This embodiment is intended to illustrate a lithium metal battery prepared using the lithium metal negative electrode of the present invention.

[0070] (1) In a glove box filled with Ar, GaI3 was dissolved in n-pentanol to prepare a 0.2 mol / L mixed solution;

[0071] (2) 50 μL of the mixed solution was sprayed on the surface of a 16 mm lithium metal disc for in-situ reaction. After the reaction was completed, the disc was dried at 80° C. in a glove box.

[0072] As a result, a lithium metal negative electrode with a composite protective layer structure is obtained, wherein the ratio of metal halide (specifically LiI): organic lithium salt (specifically lithium n-pentoxide): alloy component (specifically LiGa alloy) is 45:15:40.

[0073] In addition, the lithium metal anode is used to prepare a lithium metal battery:

[0074] The electrolyte was 1 mol / L LiPF6 EC / DEC solution, and the battery was assembled into a symmetrical battery for charge and discharge cycle testing at 1 mA / cm 2 At a current density of , the lithium deposition overpotential in the first week was 0.09 V, the average deposition overpotential during the long-term cycle was 0.06 V, and no short-circuit signal occurred after 200 cycles.

[0075] Comparative Example 1

[0076] Take a 16mm lithium metal disc and 1mol / L LiPF6 EC / DEC solution as the electrolyte, assemble it into a symmetrical battery and perform charge and discharge cycle test at 1mA / cm 2 At a current density of , the lithium deposition overpotential in the first cycle was 0.20 V, the overpotential in long-term cycling was 0.16 V, and a short circuit occurred after 70 cycles.

[0077] Comparative Example 2

[0078] Lithium was soaked in THF and dried after the reaction, leaving only organic lithium salt. The electrolyte was 1 mol / L LiPF6 EC / DEC solution, assembled into a symmetrical battery for charge and discharge cycle testing at 1 mA / cm 2 At a current density of , the lithium deposition overpotential in the first week was 0.19 V, the average deposition overpotential during the long-term cycle was 0.15 V, and a short-circuit signal appeared after 100 cycles.

[0079] Comparative Example 3

[0080] NaCl was dissolved in NMP to prepare a 0.1 mol / L solution. 50 μL of the solution was sprayed on the surface of a 16 mm lithium metal disc and dried to obtain a product with a halide: organic lithium salt ratio of 85:15. The electrolyte was 1 mol / L LiPF6 EC / DEC solution, assembled into a symmetrical battery for charge and discharge cycle testing at 1 mA / cm 2 At a current density of , the lithium deposition overpotential in the first week was 0.22 V, the average deposition overpotential during the long-term cycle was 0.14 V, and a short-circuit signal appeared after 120 cycles.

[0081] Comparative Example 4

[0082] A lithium metal negative electrode was prepared according to the same preparation method as in Example 1, except that in step (2), the conditions were changed so that the ratio of lithium halide (specifically LiCl): organic lithium salt (specifically lithium butoxide): alloy component (specifically LiAl alloy) was 10:15:75.

[0083] In addition, the lithium metal anode is used to prepare a lithium metal battery:

[0084] The electrolyte was 1 mol / L LiPF6 EC / DEC solution, and the battery was assembled into a symmetrical battery for charge and discharge cycle testing at 1 mA / cm 2 At a current density of , the lithium deposition overpotential in the first week was 0.1V, the average deposition overpotential during the long-term cycle was 0.08V, and a short-circuit signal appeared after 50 cycles.

[0085] Comparative Example 5

[0086] A lithium metal negative electrode was prepared according to the same preparation method as in Example 1, except that in step (1), "AlCl3 was dissolved in THF to prepare a 0.02 mol / L solution" was replaced by "CuCl2 was dissolved in acetone to prepare a 0.05 mol / L solution".

[0087] In addition, the lithium metal anode is used to prepare a lithium metal battery:

[0088] The electrolyte was 1 mol / L LiPF6 EC / DEC solution, and the battery was assembled into a symmetrical battery for charge and discharge cycle testing at 1 mA / cm 2 At a current density of , the lithium deposition overpotential in the first week was 0.2V, the average deposition overpotential during the long-term cycle was 0.16V, and a short-circuit signal appeared after 20 cycles.

[0089] In summary, the lithium metal battery prepared using the lithium metal negative electrode prepared in Examples 1-3 has higher cycle stability and cycle life. It can be explained that in the present invention, the combination of metal halide and organic solvent can form a protective layer of a composite structure of specific components on the surface of lithium metal, which can make the lithium metal negative electrode with a composite structure conduct lithium ions and have a certain electronic conductivity at the same time, effectively improving the uniformity of lithium ion distribution during the deposition process, thereby delaying the formation of lithium dendrites. Furthermore, the lithium metal battery containing the lithium metal negative electrode can have higher cycle stability and cycle life.

[0090] However, since Comparative Examples 1 and 2 do not use the lithium metal negative electrode with the composite structure of the present invention, the performance of the obtained lithium metal batteries is poor.

[0091] In Comparative Example 3, the metal halide specified in the present invention is not used, but NaCl is used. As it cannot be alloyed with lithium, the performance of the obtained lithium metal battery is poor.

[0092] In Comparative Example 4, since the ratio of lithium halide (specifically LiCl): organic lithium salt (specifically lithium butoxide): alloy component (specifically LiAl alloy) is 10:15:75, which is not within the range specifically defined by the present invention, the performance of the obtained lithium metal battery is poor.

[0093] In Comparative Example 5, since CuCl2 is dissolved in acetone, on the one hand, the metal selected is copper, which will lead to the problem of being unable to alloy with lithium; on the other hand, the organic solvent selected is acetone, which is not the organic solvent specifically defined in the present invention, resulting in poor performance of the obtained lithium metal battery.

[0094] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any appropriate manner. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. However, these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium metal negative electrode, characterized in that The lithium metal negative electrode comprises at least one composite protective layer, wherein the composite protective layer comprises a composition containing a lithium halide, an organic lithium salt and an alloy component, and based on the total weight of the composition, the content of the lithium halide is 25-55% by weight, the content of the organic lithium salt is 5-30% by weight, and the content of the alloy component is 30-60% by weight; The lithium halide is selected from one or more of chloride, bromide, fluoride and iodide of metallic lithium, the organic lithium salt is selected from one or more of lithium butoxide, CH3CH2OLi and lithium n-pentoxide, the alloy component is an alloy formed by lithium and a metal element, and the metal element is selected from one or more of aluminum, zinc, gallium, germanium, cadmium, indium and tin.

2. The lithium metal negative electrode according to claim 1, wherein Based on the total weight of the composition, the content of the lithium halide is 30-50% by weight, the content of the organic lithium salt is 5-25% by weight, and the content of the alloy component is 35-55% by weight.

3. The lithium metal negative electrode according to claim 1 or 2, wherein Based on the total weight of the composition, the content of the lithium halide is 35-45% by weight, the content of the organic lithium salt is 10-20% by weight, and the content of the alloy component is 40-50% by weight.

4. The lithium metal negative electrode according to claim 1 or 2, wherein The lithium halide is selected from one or more of lithium chloride, lithium bromide and lithium iodide.

5. The lithium metal negative electrode according to claim 1 or 2, wherein: The alloy component is selected from one or more of lithium aluminum alloy, lithium gallium alloy and lithium indium alloy.

6. A method for preparing a lithium metal negative electrode according to any one of claims 1 to 5, characterized in that: The preparation method comprises: (1) contacting and mixing a metal halide with an organic solvent to obtain a mixed solution; (2) contacting the mixed solution with lithium metal to perform an in-situ reaction to obtain a lithium metal negative electrode; Wherein, the metal halide is selected from one or more of chlorides, bromides, fluorides and iodides of transition metals, and the transition metal is selected from one or more of aluminum, zinc, gallium, germanium, cadmium, indium and tin.

7. The preparation method according to claim 6, wherein: The metal halide is selected from one or more of AlCl3, InBr3 and GaI3.

8. The preparation method according to claim 6, wherein: The organic solvent is selected from one or more of tetrahydrofuran and alcohol.

9. The preparation method according to claim 6, wherein: The concentration of the mixed solution is 0.01-5 mol / L.

10. The preparation method according to claim 9, wherein: The concentration of the mixed solution is 0.02-0.6 mol / L.

11. A lithium metal battery, characterized in that: The lithium metal battery comprises the lithium metal negative electrode according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Protection layer used for negative electrode of secondary lithium battery

    CN106935800A

  • Lithium negative electrode protective film, preparation method and lithium metal secondary battery

    CN109004276A

  • Lithium metal negative electrode, preparation method thereof and lithium metal battery

    CN110931711A

  • Lithium sheet with double-phase surface protection layer, and production method and application thereof

    CN112421136A